Metode Pembelajaran Pendidikan Islam yang Efektif: Studi Empiris di Sekolah Menengah - Zein, Muhammad (Peneliti.net, 2024)
This study aims to explore the effectiveness of teaching methods in Islamic Education at the secondary school level, focusing on the implementation of Problem-Based Learning (PBL), the constructivist approach, and educational technology. PBL has been shown to enhance students' critical thinking and problem-solving skills, while the constructivist approach promotes a deeper understanding of religious concepts. Educational technology plays a crucial role in increasing student engagement through mobile applications and multimedia. However, the implementation of these methods faces challenges, such as the need for more intensive teacher training and limited access to technology. This study employs a qualitative method through observation, interviews, and document analysis. The findings indicate that the combination of PBL, constructivism, and educational technology significantly improves the quality of Islamic Education, though stronger support is needed in teacher training and technological infrastructure.